Gender equality for sustainability in ports: Developing a framework. (September 2021) - Barreiro-Gen, María; Lozano, Rodrigo; Temel, Melis; Carpenter, Angela
Abstract: Ports have increasingly been addressing sustainability issues; however, gender equality has been a low priority in such efforts. This paper is aimed at providing insights into how ports have been addressing gender equality to contribute to sustainability. Twelve semi-structured interviews were conducted with top-level port managers from six European countries. The responses from the interviewees were analysed using Grounded Theory's constant comparative analysis. The findings show that European ports have engaged in gender equality measures aimed at contributing to sustainability through gender equality in five stages: (1) Gender segregation, which needs to be overcome, and is, in many cases, the starting point; (2) Compliance with national laws and regulation; (3) Gender equity; (4) Gender equality; and (5) More sustainable ports. Internal and external forces affect each of the stages, where thrust forces help ports reduce gender segregation and advance towards becoming more sustainable and drag forces slow or block the efforts and may lead to returning to a previous stage of the framework. The findings were integrated to develop a "Gender equality for sustainability in ports" framework. Gender equality is a sine qua non for ports, and other male oriented industries, in becoming more sustainable.